Immunogenicity of a new routine vaccination schedule for global poliomyelitis prevention: an open-label, randomised controlled trial. Issue 10011 (12th December 2015) - Sutter, Roland W; Bahl, Sunil; Deshpande, Jagadish M; Verma, Harish; Ahmad, Mohammad; Venugopal, P; Rao, J Venkateswara; Agarkhedkar, Sharad; Lalwani, Sanjay K; Kunwar, Abhishek; Sethi, Raman; Takane, Marina; et al.
Summary: Background: Polio eradication needs a new routine immunisation schedule—three or four doses of bivalent type 1 and type 3 oral poliovirus vaccine (bOPV) and one dose of inactivated poliovirus vaccine (IPV), but no immunogenicity data are available for this schedule. We aimed to assess immunogenicity of this vaccine schedule. Methods: We did an open-label, randomised controlled trial in four centres in India. After informed consent was obtained from a parent or legally acceptable representative, healthy newborn babies were randomly allocated to one of five groups: trivalent OPV (tOPV); tOPV plus IPV; bOPV; bOPV plus IPV; or bOPV plus two doses of IPV (2IPV). The key eligibility criteria were: full-term birth (≥37 weeks of gestation); birthweight ≥2·5 kg; and Apgar score of 9 or more. OPV was administered at birth, 6 weeks, 10 weeks, and 14 weeks; IPV was administered intramuscularly at 14 weeks. The primary study objective was to investigate immunogenicity of the new vaccine schedule, assessed by seroconversion against poliovirus types 1, 2, and 3 between birth and 18 weeks in the per-protocol population (all participants with valid serology results on cord blood and at 18 weeks). Neutralisation assays tested cord blood and sera collected at 14 weeks, 18 weeks, 19 weeks, and 22 weeks by investigators masked to group allocation. This trial was registered with the India Clinical Trials Registry, number CTRI/2013/06/003722. Findings: Of 900 newborn babies enrolled between June 13 and Aug 29, 2013, 782 (87%) completed the per-protocol requirements. Between birth and age 18 weeks, seroconversion against poliovirus type 1 in the tOPV group occurred in 162 of 163 (99·4%, 95% CI 96·6–100), in 150 (98·0%, 94·4–99·6) of 153 in the tOPV plus IPV group, in 153 (98·7%, 95·4–99·8) of 155 in the bOPV group, in 155 (99·4%, 96·5–100) of 156 in the bOPV plus IPV group, and in 154 (99·4%, 96·5–100) of 155 in the bOPV plus 2IPV group. Seroconversion against poliovirus type 2 occurred in 157 (96·3%, 92·2–98·6) of 163 in the tOPV group, 153 (100%, 97·6–100·0) of 153 in the tOPV plus IPV group, 29 (18·7%, 12·9–25·7) of 155 in the bOPV group, 107 (68·6%, 60·7–75·8) of 156 in the bOPV plus IPV group, and in 121 (78·1%, 70·7–84·3) of 155 in the bOPV plus 2IPV group. Seroconversion against poliovirus type 3 was achieved in 147 (90·2%, 84·5–94·3) of 163 in the tOPV group, 152 (99·3%, 96·4–100) of 153 in the tOPV plus IPV group, 151 (97·4%, 93·5–99·3) of 155 in the bOPV group, 155 (99·4%, 96·5–100) of 156 in the bOPV plus IPV group, and 153 (98·7%, 95·4–99·8) of 155 in the bOPV plus 2IPV group. Superiority was achieved for vaccine regimens including IPV against poliovirus type 3 compared with those not including IPV (tOPV plus IPV vs tOPV alone, p=0·0008; and bOPV plus IPV vs bOPV alone, p=0·0153). 12 serious adverse events occurred (six in the tOPV group, one in the tOPV plus IPV group, three in the bOPV group, zero in the bOPV plus IPV group, and two in the bOPV plus 2IPV group), none of which was attributed to the trial intervention. Interpretation: The new vaccination schedule improves immunogenicity against polioviruses, especially against poliovirus type 3. Funding: WHO, through a grant from Rotary International (grant number 59735 ).